The Need for Parental Support for Migrant Parents in Transition Into Sweden: A Perspective - Mangrio, Elisabeth; Enskär, Karin; Ramji, Rathi; Sjögren-Forss, Katarina; Tengland, Per-Anders; Theodoridis, Kyriakos; Zdravkovic, Slobodan; Rämgård, Margareta (Frontiers in Public Health, 2022)
Migration is a stressful experience and research shows that newly arrived migrants in Sweden suffer from different challenges and struggle to relate to parenting in a new culture that is different from their own. The Swedish Child Health Services (CHS) focuses on promoting health among children, as well as supporting parents in parenting. Although this is a goal, migrant parents participate at lower rates in parental support groups. This paper aims to discuss how the Swedish CHS can support these families and address the need for improvement in the parental support offered to migrant parents during transition into their host country. The Swedish government decided to place greater emphasis and resources on supporting parents and promoting equal health among families in Sweden, with special emphasis on migrants and other vulnerable groups. This report from the Swedish government indicates the importance of creating knowledge about new ways, methods, and actions that may be needed to increase this support. One suggestion of this paper is to provide culturally appropriate healthcare work using a community-based participatory research approach, where migrant parents themselves are actively involved in the development of support programs. This approach will not only provide migrant families knowledge and support, it will also build on their needs and the challenges they can share, and receive support to overcome.